Case Report : Chromoblastomycosis - Handayani, Melina; Topik, Mohamad Mimbar (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Chromoblastomycosis is a recurring deep mycosis of the skin and subcutaneous towel. Clinical features are characterized by verrucous shrine lesions, especially in the lower extremities. This disease is usually preceded by trauma in the form of a wound which is the initial implantation of the fungus. The fungus will be implanted in the dermis and will infect the skin with the subcutaneous towel. Chromoblastomycosis is caused by a fungus from the Dematiaceae family. Although Chromoblastomycosis occurs worldwide, it is most common (>70%) in tropical and subtropical regions. Case Presentation: We present a case in which a 72-year-old man came to the dermatovenereology polyclinic with the main complaint of thickening of the skin in the plantar of the right leg, the surface is rough, the skin looks dry, it doesn't itch and it doesn't hurt, it gets worse over time, widened. Based on the histopathology, the appearance of the epidermis in the form of pseudoepitheliomatous hyperplasia, hyperkeratosis, acanthosis, microabscesses with neutrophil inflammatory cells, lymphocytes, multinucleated giant cells, and spores. In the dermis, microabscesses were found, and no necrosis was seen. Conclusion: The diagnosis was chromoblastomycosis. This patient was given oral antimycotic Itraconazole 2 x 200 mg/day. There was a clinical improvement.